PENDAMPINGAN IMPLEMENTASI PEMBELAJARAN BERORIENTASI ECOLITERACY DI SEKOLAH DASAR - Salimi, Moh; Hidayah, Ratna; Karsono, Karsono; Fauziah, Muna; Astuti, Dewi (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
Sustainable development as part of Natural Resource conservation needs to be implemented properly, one of which is through the ecoliteracy movement, so that students are expected to have a good understanding of the environment. This community service activity aims to develop ecoliteracy-oriented learning. This mentoring activity was carried out at Wonorejo 1 Public Elementary School, Kebumen Regency. The subjects in this mentoring activity included the principal, teachers, and school supervisors. Mentoring and training were used in this community service model. This mentoring was implemented in three main stages, namely the mass teaching method, the group teaching method, and the individual teaching method. The activity procedures included fulfilling partnerships, training on the implementation of ecoliteracy-oriented learning, and the implementation of ecoliteracy-oriented learning in upper and lower grades. The findings showed that the ecoliteracy-oriented learning process was implemented smoothly through the In, On, and In scheme. Ecoliteracy-oriented learning produces (1) a quality learning process, characterized by a variety of enjoyable learning activities and continuously developing ecoliteracy competencies, and (2) mentoring activities have an impact on learning activities including increasing student-to-student interactions and student interactions with media as well as increasing ecoliteracy in the head/cognitive, hands/activity, and heart/emotional aspects. Integrating environmental knowledge into formal education, providing direct experience, and fostering empathy and inclusivity. Schools can develop students who are not only environmentally aware but also proactive in implementing sustainable practices.